Integrasi Analisis SROI, IKM, dan SEM-PLS dalam Evaluasi Program CSR Pemberdayaan Masyarakat Hutan Adat - Prasetyo, Widyanto Hadi; Febrianda, Febrianda; Hatta, Ichramsyah Fajar; Usman, Marzuki; Jantiningrum, Pawestri Cendani; Kurniyanto, Romi (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2026)
This study integrates Social Return on Investment (SROI), the Community Satisfaction Index (CSI), and Structural Equation Modeling–Partial Least Squares (SEM-PLS) to evaluate the effectiveness of the Corporate Social Responsibility (CSR) program implemented by PT PLN (Persero) UIP Kalimantan Bagian Barat in the Rungan Indigenous Forest area, Central Kalimantan. This approach aims to quantitatively and qualitatively assess the social, economic, and environmental impacts of a community empowerment program grounded in conservation principles and local wisdom. The research employs a descriptive–explanatory design with 76 indigenous respondents selected through purposive sampling. The results show an SROI ratio of 3.43, indicating that every Rp1.00 invested generates Rp3.43 in socio-economic benefits. The CSI score reached 3.565, equivalent to a converted value of 89.128 in category A (very good), reflecting a high level of satisfaction with the quality of program implementation. The SEM-PLS analysis reveals that institutional support and social capital significantly influence community empowerment, with access and capability acting as key mediators. The integration of these three methods provides a comprehensive, measurable, and evidence-based CSR evaluation framework, which is relevant for replication in other indigenous forest areas and supports the achievement of the social and environmental pillars of the Sustainable Development Goals (SDGs).